Teaching self‐management strategies to upper‐elementary students: Evidence of promise from the We Have Choices program. Issue 6 (13th April 2022) - Smolkowski, Keith; Marquez, Brion; Marquez, Jessie; Vincent, Claudia; Pennefather, Jordan; Walker, Hill; Strycker, Lisa A.
Abstract: Student behavior problems in general‐education classrooms present a major barrier to effective teaching. Behavior challenges, such as disruptions, noncompliance, and peer conflicts, reduce instructional time, whereas prosocial behaviors, such as paying attention, being ready to work, asking for help, participating in class, and completing homework, improve academic performance. Most interventions developed to address student behavior problems were not designed for general‐education students in typical classrooms. The purpose of this paper is to present preliminary results from a novel intervention developed to enhance behavioral self‐management skills among all upper‐elementary students in general‐education classrooms. We Have Choices, a universal intervention, was designed to increase students' capacity to make appropriate behavioral choices and decrease teachers' responsibility by transferring behavior management to students. An initial randomized controlled trial with 86 fourth‐ to sixth‐grade teachers and 2055 students suggested that We Have Choices was associated with improvements in student‐reported use of self‐management strategies, teacher‐reported student prosocial behavior, and teacher‐reported self‐efficacy in behavior management and instruction. Teachers gave the program high scores for social validity, suggesting a good fit for their classrooms. Highlights: We Have Choices was developed to teach upper‐elementary students behaviors intended to support academic success (e.g., ask for help, participate in class) and to transfer the management of those behaviors to the students. Teachers' use of We Have Choices predicted improved student‐reported use of self‐management strategies and, for students who initially struggled with classroom behavior, improved teacher‐reported use of the skills taught by the program. Teachers who used We Have Choices reported improved self‐efficacy for behavior management and instruction.